The Negative Feedback of the Glutamine/Prostatitis Loop Identified Among 1400 Metabolites and Prostatitis via Mendelian Randomization - Yi Wang; Hao Ji; Yingfei Chen; Bingye Zhu; Yongming Peng; Qianwei Xing (Mediators of Inflammation, 2025)
Conclusion: Four metabolic etiologies, two metabolic phenotypes, and the glutamine/prostatitis negative feedback loop were first identified by us for prostatitis in the European population to better understand its etiologies and offer novel treatment targets.